Mesenchymal Stem Cell Transplantation in Liver Diseases - Nevens, Frederik; van der Merwe, Schalk (Seminars in Liver Disease, 2022)
Promising preclinical data suggested that bone marrow–derived mesenchymal stem cells (BM-MSC) can reduce hepatic fibrosis and stimulate liver regeneration. Preclinical studies moreover suggested that the immunomodulatory and anti-inflammatory functions of MSCs may reduce hepatic inflammation, improve liver function, and decrease infection incidences which are deemed especially important in the case of acute-on-chronic liver failure (ACLF). Studies in patients with decompensated cirrhosis demonstrated that injection of BM-MSC resulted in an improvement of biochemical tests and led to a survival benefit in ACLF. Most of these studies were performed in hepatitis B virus infected patients. However, two adequately powered studies performed in Europe could not confirm these data. A possible alternative to mobilize BM-MSC into the liver is the use of granulocyte colony-stimulating factor (G-CSF) which has proregenerative and immunomodulatory effects. In Indian studies, the use of G-CSF was associated with improvement of survival, although this finding could not be confirmed in European studies. Human allogeneic liver-derived progenitor cell therapy represents a potential treatment for ACLF, of which the main action is paracrine. These human liver–derived MSC can perform various functions, including the downregulation of proinflammatory responses. The clinical beneficial effect of these cells is further explored in patients with alcoholic cirrhosis and ACLF in Europe.
Keywords: liver cirrhosis; ACLF; alcoholic hepatitis; human allogeneic liver progenitor cells